Cyber Empathy as a Digital Shield Against Cyberbullying: A Systematic Literature Review - Ibrahim, Abdul Rahman (Jurnal Konseling dan Psikologi Indonesia, 2025)
This study systematically reviews the relationship between empathy both cognitive and affective and cyberbullying in publications from 2020 to 2024. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. Searches in Google Scholar and Scopus using the keyword “cyber empathy” yielded 271 articles; eight empirical studies met the inclusion criteria of topic relevance, scholarly type, and publication year. The synthesis shows that empathy consistently functions as a protective factor, reducing involvement in cyberbullying as either perpetrator or victim. Cognitive empathy demonstrates a stronger preventive influence than affective empathy, underscoring the importance of perspective-taking in limiting online aggression. Additional variables such as moral disengagement, family support, and self-regulation emerge as mediators or moderators, enriching the theoretical understanding of empathy in digital contexts. The novelty of this review lies in its cross-cultural scope, covering studies from Germany, Indonesia, the Philippines, South Korea, Costa Rica, Iran, and Turkey, which are rarely examined in recent reviews. These findings provide an empirical foundation for empathy-based interventions, including cognitive perspective-taking training and family engagement, while informing digital literacy policies and school character education. Strengthening digital empathy is therefore a key strategy to prevent cyberbullying across diverse cultures.